REVITALISASI SOCIAL EMOTIONAL LEARNING (SEL) DALAM PENDIDIKAN ISLAM: INTEGRASI PENDEKATAN HOLISTIK UNTUK KEBAHAGIAAN DAN KETAHANAN MENTAL SISWA - Celine, Devi Rofidah; Iksan Kamil Sahri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This research aims to revitalize the concept of Social Emotional Learning (SEL) in Islamic education through a holistic approach that integrates spiritual, social, and emotional values. This research is motivated by the increasing issue of mental health and happiness crisis among students, as well as the gap between the secular SEL approach and the spiritual dimension of Islamic education. The research method used is a literature study with content analysis to examine literature related to SEL, Islamic education, holistic approach, and the concept of happiness and mental resilience of students. The results showed that the revitalization of SEL in Islamic education can be done by integrating Islamic values such as ṣabr, tawakkal, amanah, and rahmah into SEL competencies. This integration not only strengthens the moral dimension of students, but also builds a deep inner connection with religious teachings, thus increasing students' happiness and mental resilience. The integration model of SEL and Islamic spiritual values presented in this study can be adopted by Islamic educational institutions as a framework for developing students' social-emotional competencies holistically.